Analisis Hermeneutik Doa Yesus dalam Yohanes 17:20-23 dan Implikasinya bagi Kehidupan Antarumat Beragama di Indonesia - Afrina Jeliyanti Sirait; Raulina (Institut Agama Kristen Negeri Palangka Raya, 2026)
This paper discusses the theological meaning of Jesus' prayer in John 17:20-23. The main focus of this prayer is Jesus' request that His followers live in unity as the unity between Jesus and the Father. This study aims to analyze the message of unity contained in John 17:20-23 through a critical hermeneutical approach supported by various literary sources. The results of this study indicate that the unity referred to by Jesus is not only spiritual and internal among the disciples, but also has a public dimension of unity, where unity reflects love rooted in the relationship between the Father and the Son. A critical hermeneutical study of John 17:20-23 shows that Jesus' prayer regarding the unity of the disciples emphasizes that the unity of believers is a sign of God's presence and a means for the world to recognize that the world is sent by the Father. In the context of interfaith life in Indonesia, the unity taught by Jesus becomes the basis for Christians to build a dialogical attitude, tolerance, and respect for differences in interfaith life. Thus, this study seeks to contribute theological thought regarding the importance of Christians being peacemakers, maintainers of harmony, and playing an active role in creating a harmonious social life in a pluralistic society.